(untitled) (Swiss Medical Weekly, 2025)
BACKGROUND: The prevalence of cancer is rising continuously worldwide. Relatives play an important role in caring for cancer patients and are at the same time affected by the illness and treatment of their loved ones. They have often been referred to as a forgotten group. Advances in digital technology offer various opportunities to enhance the well-being of and care for relatives. OBJECTIVES: The aim of the study was to investigate the utility of a mobile application to support the relatives of palliative cancer patients in Switzerland, the potential content elements of such an app, and its optimal functional and structural design. METHOD: Using a purposive sampling strategy, three focus group discussions were conducted at the University Hospital of Bern. The 15 participants included both relatives and experts. Data was analysed using content structuring qualitative content analysis according to Kuckartz and Rädiker. RESULTS: Statements from the focus groups were summarised in four main categories. These included statements from participants about the need for and potential benefits of an app, such as resource gains or easier access to care. Statements regarding possible content components of the app, such as tools for professional support and coordination or the provision of information, were also summarised. Statements were also included on the necessary functional features and the structural embedding of the app. CONCLUSIONS: The results indicate a need for a caregivers app in Switzerland. The app should reduce gaps in care, focus on family members, and strengthen their empowerment and access to resources. In terms of content, bundled information, low-threshold support offers, coordination tools, and self-care options should be guaranteed. The modular and simply structured app should be designed in a needs-oriented manner to be used safely throughout Switzerland.